HIV / AIDS and macroeconomical performance: Empirical evidence from Kenya - Ishioro, Bernhard O. (Univerzita Pardubice, 2016)
This paper contributes to the investigation and exploration of the impacts of HIV/AIDS on the economic performance of Kenya. It evaluates the HIV/AIDS profile and socio-economic performance of the Kenyan economy before and during the epidemic era. The paper attempted a robust examination of the relationship between HIV/AIDS and major economic, education, demographic and health indicators in Kenya. The paper applied the step by step Wiener-Granger causality tests; and found that HIV/AIDS Granger-causes tuberculosis, life expectancy at birth, population growth, gross primary school enrolment and economic growth while urbanization, proportion of population under 15 years, rural population and gross primary school enrolment were identified as the determinants of the prevalence of HIV/AIDS in Kenya. The paper recommends a combined HIV mitigation surveillance approach and a post epidemic reconstruction of both human and social capital.
Keywords: HIV/AIDS epidemic; economic growth; Kenya; Wiener-Granger causality; O15; J11; C18